Aspectos do neurodesenvolvimento, sistema estomatognático e distúrbios alimentares em lactentes com trissomia do 21 - Pinheiro, Denilma Lígia da Silva Alves (2023)
Introduction: Trisomy 21 is characterized by being a genetic condition caused by the presence of an extra. The delay in the development of children with T21 can occur due to multiple factors, as a result of the cognitive and neurological alterations inherent to the syndrome; the lack of adequate stimuli during the mother-infant interaction; delayed neuropsychomotor development; breathing, heart and hearing problems; and changes in the stomatognathic system. Objective: to observe the implications between the neurodevelopment process, the stomatognathic aspects and feeding difficulties in babies with trisomy 21 using the application of the Denver II, Amiofe-E Infants and the Brazilian Infant Feeding Scale, in order to guide the skills acquired and non-acquired to objectify therapeutic planning. Method: This is an analytical cross-sectional study, of a quantitative nature, which will use an inductive approach and statistical comparative procedure. Direct documentation technique will be used, with application of Protocol and record of results. Results: The study found, through the crossing of the Denver II Test, Infant Amiofe-E and EBAI, associations between delays in neurodevelopmental skills, the structures of the stomatognathic system and complaints from parents and/or guardians about the feeding of infants with T21. Conclusion: The importance of early screening of skills and changes in the population with T21, leads the team to formalize an effective therapeutic planning, focused on their individual needs in order to promote evolution in a clinical environment.